2020
DOI: 10.21037/atm-20-5168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined chronic predictable and unpredictable stress on depression-like symptoms in mice

Abstract: Background: Mental stress mainly induces depression, and predictable stress, as well as a constant bombardment of chronic unpredictable micro-stressors, always coexist in daily life. However, the combined effect of predictable and unpredictable stress on depression is still not fully understood. Methods:The chronic restraint stress (CRS) is to restrain the mice for 6 h per day for 3 weeks, and the chronic unpredictable mild stress (CUMS) is to stimulate the mice with 7 different stressors for 3 weeks. We evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
6
23
0
1
Order By: Relevance
“…The animal experiments revealed that LPS activated microglia promoted the production of proinflammatory cytokines in the brain and induced anxiety-like behavior [ 55 ], while cotreatment with antibiotic doxycycline could attenuate LPS-induced microglial activation and anxiety in mice [ 58 ]. In this study, OCA significantly reduced neuropsychiatric disorders-related bacteria in the HFHS-fed MDs mice, such as Marinifilaceae, Rikenellaceae and its genus Alistipes , and these microbes have been reported in the previous model and clinical studies [ 59 , 60 , 61 ]. For example, the indole-positive Alistipes could influence the tryptophan metabolism and disrupt the balance of the serotonergic system [ 61 ], which was known to modulate neuronal signals related to anxiety [ 62 ].…”
Section: Discussionsupporting
confidence: 62%
“…The animal experiments revealed that LPS activated microglia promoted the production of proinflammatory cytokines in the brain and induced anxiety-like behavior [ 55 ], while cotreatment with antibiotic doxycycline could attenuate LPS-induced microglial activation and anxiety in mice [ 58 ]. In this study, OCA significantly reduced neuropsychiatric disorders-related bacteria in the HFHS-fed MDs mice, such as Marinifilaceae, Rikenellaceae and its genus Alistipes , and these microbes have been reported in the previous model and clinical studies [ 59 , 60 , 61 ]. For example, the indole-positive Alistipes could influence the tryptophan metabolism and disrupt the balance of the serotonergic system [ 61 ], which was known to modulate neuronal signals related to anxiety [ 62 ].…”
Section: Discussionsupporting
confidence: 62%
“…This can represent a picture of stressors that occur both mild, moderate, and severe (Weisbrod et al, 2019). Mental stress can lead to depression (Qiao et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…OPCs persist throughout the postnatal period and continue to divide and generate myelinating OLs throughout their lifespan ( Bergles and Richardson, 2016 ). While our study focused on immature and mature myelinating OLs, stress can also affect the progenitor pool in these limbic regions ( Qiao et al, 2020 ; Saul et al, 2015 ; Teissier et al, 2020 ). For example, repeated variable stress selectively reduced the number of proliferating OPCs in the AMY in juvenile male mice, while leaving proliferating neurons unchanged ( Saul et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%